Respond of the Growth and Production of Local Upland Rice Cultivars Sultra to the WateringVolume - Borromeu, Moizes dos R.; I Gusti R. Sadimantara; Yulius B. Pasolon (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the study was to find out the respond growth and production of local upland rice Sultra’s on the watering volume. The research was conducted in green house sized 4x10 m, from April to August 2015. This study tested four (4) cultivation local upland rice Sultra in the pot and treated with sub-optimum and optimal water levels of 25%, 50%, 100% and 150%. The experiment was conducted by using factorial desing of two factors of randoming complete block design (RCBD) with three replications, where first factor is W (water level) is comprised of four levels; W1 (25%), W2 (50%), W3 (100%), and W4 (150%). Second factor is cultivars upland rice local comprised of four levels; V1 (cultivar pae dai Ngalaru), V2 (cultivar pae Uba), V3 (cultivar pae Bou) and V4 (cultivar pae Bandoeha). The parameter observed were t plant height of the number of maximum tiller, number of leave, dry weight, dry weight of root, number of productive tiller, days to flowering, weight of 1000 rice, number of grain per tiller, the percentage of empty grain per tiller (%), blossoming age, and number of dry grain per tree